Comparison of phenotypic and phytochemical profiles of 20 Lycium barbarum L. goji berry varieties during hot air-drying - Ting Huang; Ning Jia; Lunxuan Zhu; Wen Jiang; Aobai Tu; Ken Qin; Xiaojin Yuan; Juxiu Li (Food Chemistry: X)
The variety and drying stage of goji berries (GBs) may affect their final physical and chemical properties. This study investigated the differences in physical phenotypic parameters and major chemical composition parameters of 20 GBs varieties during four stages of hot air-drying (HD). The results indicated that the color difference values L*, a*, and b* decreased during the HD process. The contents of all amino acids decreased, with significant reductions in amino acids involved in the Maillard reaction. Correspondingly, the level of 5-hydroxymethylfurfural, a Maillard chemical reaction intermediates, increased. Furthermore, the decreased L* values were closely linked to the decomposition of carotenoids. Notably, the differences in constituents among different varieties of dried GBs were smaller than those in fresh GBs. These findings provide a theoretical basis for optimization of the GBs drying process, contributing to the expansion of GBs breeding programs and their use in global functional food and pharmaceutical industries.